Analisis Penegakan Hukum Terhadap Kasus Perusakan Hutan Mangrove di Desa Kwala Serapuh, Kabupaten Langkat - Clarentia, Celine; Rosmalinda; Affila (PT. Meja Ilmiah Publikasi, 2026)
The case of mangrove forest destruction in Kwala Serapuh Village, Langkat Regency, reflects the weakness of environmental law enforcement in Indonesia despite the existence of a strong legal framework. This study aims to analyze the delays and injustices in law enforcement related to mangrove destruction and to identify institutional and political factors contributing to the problem. This research employs a normative juridical method with a case study approach focusing on the implementation of Law Number 32 of 2009 concerning Environmental Protection and Management. The analysis reveals a significant gap between law in books and law in action due to weak inter-agency coordination, ineffective sanctions, and the dominance of economic interests over ecological protection. As a result, coastal communities have become the most affected and have lost their legal protection. The study concludes that institutional reform, stronger enforcement mechanisms, and enhanced community participation are urgently needed for environmental restoration. It recommends a stronger political commitment to prioritize ecological justice as a fundamental principle of sustainable development in Indonesia. Keywords : law enforcement, mangrove, ecological justice, environmental law, Kwala Serapuh